The Effect of Push-Up Training on the Long Service Ability in Badminton among Elementary School Extracurricular Students - Mercy Sarumaha; Khairul Usman; Ika Endah Puspita Sari; Alan Alfiansyah Putra Karo Karo (Journal Of Sport Education (JOPE), 2025)
Problems in badminton learning and training in elementary schools are still commonly found in long service skills, such as incorrect stroke techniques, lack of arm strength, and inaccurate shuttlecock direction. One form of physical training that is thought to affect long service skills is push-up training. This study aims to determine the effect of push-up training on long service skills in elementary school extracurricular students. The research method used is a quantitative method with a one-group pretest-posttest experimental design. The research subjects consisted of 15 fourth and fifth grade students who participated in badminton extracurricular activities at UPT SD Negeri 060879. Data collection techniques were carried out through a badminton long service test conducted before (pretest) and after (posttest) the push-up training treatment for six weeks. The data were analyzed using descriptive and inferential statistical analysis. The results showed an increase in badminton long service ability after push-up training, with a pretest average score of 22.06 and an increase to 39.46 on the posttest. These findings indicate that push-up training has a positive effect on improving students' badminton long service ability. Thus, push-up training can be used as an alternative physical exercise to support the improvement of basic badminton skills in elementary schools.